(untitled) (Journal of Student Affairs in Africa, 2022)
In many countries and universities, students engage in activities to promote social justice through inclusion, diversity, epistemic freedom and decolonisation, paying renewed attention to intersectionalities of race/ethnicity, class, gender and sexuality. In this special issue, we seek to focus on the translocal dimensions of student activism for equality and greater social justice. We understand ‘activism’ quite broadly to include student-led activities – ranging from small-scale mundane initiatives to large-scale protest events – that aim to change everyday life, practices or norms at the university and beyond. Students’ activist engagement is often shaped in and through translocal/ transnational/international/global spaces in which geo-political imaginaries, academic theories, actionable knowledge or symbols, hashtags, materiality and people circulate and move across socio-political contexts. Struggles are connected across multiple scales, and partially common worlds and horizons are created.